Monitoring of Deformations in Open-pit Mines and Prediction of Deformations with the Grey Prediction Model - Tasci, Levent; Tuncez, Muhammet (Research Information Ltd, 2018)
The slopes developed during open pit mining works, and consequently occurring landslides due to slope failures may lead to loss of lives, injuries and economic losses. In order to reduce or neutralize the adverse effects of landslides mentioned above, it is vital to monitor them and unravel their mechanisms. In this study, landslide-monitoring works, which were conducted in an area with a landslide potential in the working area, and the acquired results of one of the most important open-pit mines, tine Alipasa, were mentioned. In the study, deformation predictions were made based on the data gathered by using Robotic Total Station for the constant monitoring of landslides and measurements of pressure, temperature and rain. Additionally, the multivariable grey model was adopted in the prediction of deformation scales. The results acquired from geodetic and multivariable grey model were presented in the study. In the light of the data acquired by geodetic and multivariable grey model predictions, meaningful movements were detected in the analyzed area and it was observed that the results acquired from both of the methods were in line with each other.
Keywords: Landslide; Deformation; Grey Prediction Model; Geodetic Measurements